Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=x^2+x-3x-3.=x\times\left(x+1\right)-3\times\left(x+1\right)=\left(x+1\right).\left(x-3\right)\)
\(x^2-2x-3\)
\(=x^2-3x+x-3\)
\(=x\left(x-3\right)+\left(x-3\right)\)
\(=\left(x-3\right)\left(x+1\right)\)
Sửa lại đề là: \(3x^2+10x+3\)
\(=3x^2+9x+x+3\)
\(=\left(3x^2+9x\right)+\left(x+3\right)\)
\(=3x.\left(x+3\right)+\left(x+3\right)\)
\(=\left(x+3\right).\left(3x+1\right)\)
Ta có: \(\left(a-b\right)\left(b-c\right)\left(a-c\right)+\left(a+b\right)\left(b+c\right)\left(a-c\right)+\left(a+b\right)\left(a+c\right)\left(c-b\right)\)
\(=\left(a-c\right).\left[\left(a-b\right)\left(b-c\right)+\left(a+b\right)\left(b+c\right)\right]+\left(a+b\right)\left(a+c\right)\left(c-b\right)\)
\(=\left(a-c\right).\left(ab-ac-b^2+bc+ab+ac+b^2+bc\right)+\left(a+b\right)\left(a+c\right)\left(c-b\right)\)
\(=\left(a-c\right).\left(2ab+2bc\right)+\left(a+b\right)\left(a+c\right)\left(c-b\right)\)
\(=2b.\left(a-c\right).\left(a+c\right)+\left(a+b\right)\left(a+c\right)\left(c-b\right)\)
\(=\left(a+c\right)\left[2b\left(a-c\right)+\left(a+b\right)\left(c-b\right)\right]\)
\(=\left(a+c\right)\left(2ab-2bc+ac-ab+bc-b^2\right)\)
\(=\left(a+c\right)\left(ab-bc+ac-b^2\right)\)
\(=\left(a+c\right)\left[a.\left(b+c\right)-b.\left(b+c\right)\right]\)
\(=\left(a+c\right)\left(a-b\right)\left(b+c\right)\)
Ta có: \(-8x^2+23x+3\)
\(=\left(-8x^2+24x\right)-\left(x-3\right)\)
\(=-8x\left(x-3\right)-\left(x-3\right)\)
\(=\left(-8x-1\right)\left(x-3\right)\)
\(=\left(3-x\right)\left(8x+1\right)\)
\(-8x^2+23x+3\)
\(=-\left(8x^2-23x-3\right)\)
\(=-\left(8x^2-24x+x-3\right)\)
\(=-\left[8x\left(x-3\right)+\left(x-3\right)\right]\)
\(=-\left(8x+1\right)\left(x-3\right)\)
Bài làm:
1) Ta có: \(2x^2+5xy+2y^2\)
\(=\left(2x^2+4xy\right)+\left(xy+2y^2\right)\)
\(=2x\left(x+2y\right)+y\left(x+2y\right)\)
\(=\left(2x+y\right)\left(x+2y\right)\)
2) Ta có: \(2x^2+2xy-4y^2\)
\(=\left(2x^2-2xy\right)+\left(4xy-4y^2\right)\)
\(=2x\left(x-y\right)+4y\left(x-y\right)\)
\(=2\left(x+2y\right)\left(x-y\right)\)
\(1)2x^2+5xy+2y^2=2x^2+4xy+xy+2y^2=\left(2x^2+4xy\right)+\left(xy+2y^2\right)=2x\left(x+2y\right)+y\left(x+2y\right)=\left(2x+y\right)\left(x+2y\right)\)\(2)2x^2+2xy-4y^2=2x^2+4xy-2xy-4y^2=\left(2x^2-2xy\right)+\left(4xy-4y^2\right)=2x\left(x-y\right)+4y\left(x-y\right)=\left(2x+4y\right)\left(x-y\right)\)
Bạn ơi xem lại đề và yêu cầu đề nha